EXPLORING THE LIFE OF PATIENT DATA IN THE UK HEALTHCARE SECTOR - Medina Perea, Itzelle Aurora; Cox, A; Bates, J (AoIR Selected Papers of Internet Research, 2020)
In “the datafication era” the nature of data and the ways in which data is collected, processed, and shared is being drastically transformed. In the UK healthcare sector, patient data is being used in new ways and moved across different settings. Patient data is used to deliver care to patients, but at the same time is increasingly also being used for purposes beyond the direct care of patients, for example: healthcare planning, development of policy, research in academic institutions, as well as uses outside the health care sector such as for commercial and immigration enforcement purposes. The use of patient data in certain contexts outside the healthcare sector is certainly a matter of concern for the society, as it can raise significant privacy and power issues. In the context of increasing concern about privacy and power around health data, this research is an in-depth qualitative study of health “data journeys” examining the enablers and frictions of data flowing from the NHS to various academic institutions to be reused for research purposes. The research seeks to generate new knowledge about how and why socio-cultural factors shape patient data flows within the healthcare sector, and what this means for how data flows bring patient into different forms of relation with other social actors. These insights will be used to develop recommendations for “just” practices in data sharing to make patient data flows within the health sector more clear and transparent for the public.